Approximation of building window properties using in situ measurements. (February 2020) - Feng, Yanxiao; Duan, Qiuhua; Wang, Julian; Baur, Stuart
Abstract: From the perspective of homeowners, retrofitting home windows, especially for old houses, would not only facilitate energy savings but also may increase thermal comfort. To make decisions of window retrofitting or replacements, measuring and knowing the existing windows' performance level would become an essential step for the decision-making process. The study of in situ measurements of the thermal and optical performance of the glazing system in residential buildings has not been examined thoroughly. For this purpose, in this project, a portable and easy-to-use in situ measuring system for building windows using the Arduino platform and low-cost sensors have been studied, fabricated, and then examined. It is designed specifically to in situ measure the glazing properties, including Center-of-glass U-factor, Solar Transmittance (τs ), and Visible Light Transmittance (VT). We devised the measurement system and associated sensors based on thermodynamic equations and intended to simplify the measuring procedures. For general use by homeowners, this device enables a simple, quick, and reliable in situ approximation of glazing properties, with about 97.2%, 93.3%, and 92.1% accuracy for VT, τs, and Center-of-glass U-factor, respectively. The developed system and procedure can further be combined with energy estimation algorithms to support the decision-making in retrofitting building windows. Highlights: Knowing the existing windows' performance is essential to make decisions of window retrofits. A portable and easy-to-use in situ window measurement system is fabricated and tested. Low-cost, 3D printed, Arduino-based sensor module with reliable in situ approximation. The quasi-steady-state approximation is proposed and self-examined by the designed system.